The Unfeathered Bird - Van Grouw, Katrina, 1965- (Book collections on Project MUSE., 2013)
There is more to a bird than simply feathers. And just because birds evolved from a single flying ancestor doesn't mean they are structurally all the same. With over 385 stunning drawings depicting 200 species, The Unfeathered Bird is a richly illustrated book on bird anatomy that offers refreshingly original insights into what goes on beneath the feathered surface. Each exquisite drawing is made from an actual specimen and reproduced in sumptuous large format. The birds are shown in lifelike positions and engaged in behavior typical of the species: an underwater view of the skeleton.